Implementasi dan Kinerja Sistem Informasi Dokumen Online (Si-DOI) di Dinas Kependudukan dan Pencatatan Sipil Kota Palangka Raya - Muhammad Diky Andreyansyah; Said Pullah; Muhammad Iqbal Fudiatama; Muhammad Arief Taopan; Kamal Hasuna (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The Online Document Information System (Si-DOI) represents a digital innovation aimed at improving the quality of population administration services. This research analyzes the implementation and performance of Si-DOI at the Population and Civil Registration Office of Palangka Raya City. The research methodology employs a qualitative descriptive approach with a case study design, utilizing data collection techniques through in-depth interviews, observation, and documentation. Research respondents include office employees, service users, and relevant stakeholders. The findings indicate that Si-DOI implementation has facilitated document access, accelerated administrative processes, and enhanced public service transparency. However, several technical constraints and infrastructure limitations still require improvement. The research recommends system capacity enhancement, human resource development, and continuous updates to optimize Si-DOI performance. The conclusion suggests that Si-DOI has the potential to become an effective population administration information system, but requires ongoing commitment to development and improvement.